Normative values of skeletal muscle mass, strength and performance in the Indian population - Sidhu, Sandeep Singh; Saggar, Kavita; Goyal, Omesh; Kishore, Harsh; Sidhu, Samarth Singh (Indian journal of gastroenterology : official journal of the Indian Society of Gastroenterology, 2024)
BACKGROUND AND OBJECTIVES: Skeletal muscle is characterized by its mass, strength and performance. These normative values are pivotal in defining sarcopenia. Sarcopenia is associated with poor outcome of numerous medical and surgical conditions. This study aimed to establish normative benchmarks for skeletal muscle mass, strength and performance within the context of the Asian (Indian) population. METHODS: Our investigation utilized the computed tomography (CT) skeletal muscle index (SMI), handgrip strength (HGS), gait velocity and chair-stand test to construct reference values for muscle characteristics in the Indian population. RESULTS: The SMI analysis incorporated 1485 cases of acute abdomen (54.7%) males). The calculated SMI (kg/m2) was 38.50 (35.05-42.30) in males and 36.30 (32.20-41.20) in females (p = 0.510). The study also involved 3083 healthy individuals (67.6% males) evaluated for muscle strength and performance between August 2017 and August 2018. Notably, HGS (kg force) was recorded at 34.95 (26.50-43.30) in males and 25.50 (18.60-31.20) in females (p < 0.001). Gait velocity (metres/second) exhibited values of 1.25 (1.04-1.56) in males and 1.24 (1.03-1.56) in females (p = 0.851). Additionally, chair-stand test (seconds) results were 10.00 (9.00-13.00) in males and 12.00 (10.00-14.00) in females (p < 0.001). CONCLUSIONS: The investigation determined that males had greater muscle strength and performance than females. But gender wise, there was no significant difference in muscle mass. Interestingly, our population's muscle parameters were consistently lower compared to western literature benchmarks. These normative values will help to define sarcopenia parameters in our population, which have prognostic value in multiple ailments.
Keywords: síla ruky; Walking Speed; dospělí; kosterní svaly; Hand Strength; Female; Adult; mladý dospělý; ženské pohlaví; Tomography, X-Ray Computed; svalová síla; Adolescent; India; lidé; Muscle, Skeletal; referenční hodnoty; Muscle Strength; Middle Aged; rychlost chůze; Male; Aged; Reference Values; Young Adult; počítačová rentgenová tomografie; lidé středního věku; senioři; mužské pohlaví; sarkopenie; Indie; Sarcopenia; mladiství; Humans